2001
DOI: 10.1046/j.1440-1681.2001.03512.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Milrinone On Left Ventricular End‐Systolic Pressure–Volume Relationship Of Rat Hearts In Situ

Abstract: 1. We have already shown that the left ventricular (LV) end-systolic pressure-volume relationship (ESPVR) of rat hearts in situ is an upward convex curve and that LV end- systolic pressure (ESP(mLVV)) and the systolic pressure-volume area (PVA(mLVV)) at a mid-range LV volume (mLVV) sensitively reflect acute changes in LV contractility and work capability. Milrinone is a non-glycosidic, non-sympathomimetic drug that increases myocardial cAMP concentrations by selective inhibition of cardiac phosphodiesterase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Previous studies have revealed that the left ventricular end-systolic pressure-volume relation of isolated crosscirculated and in situ ejecting adult rat hearts have upward convex curves, even within the physiological range [15][16][17]. This convex curvature of end-systolic pressure-volume relation has also been described in mice hearts [18,19].…”
mentioning
confidence: 70%
“…Previous studies have revealed that the left ventricular end-systolic pressure-volume relation of isolated crosscirculated and in situ ejecting adult rat hearts have upward convex curves, even within the physiological range [15][16][17]. This convex curvature of end-systolic pressure-volume relation has also been described in mice hearts [18,19].…”
mentioning
confidence: 70%
“…Both of them have been approved by the United States Food and Drug Administration and are used in clinical treatment. The former is prescribed in patients with severe heart failure (Kikura and Levy, 1995; Kishi et al, 2001); the latter is used in patients with intermittent claudication (Beebe et al, 1999). The potency of inhibition of milrinone and cilostazol on PDE3A is similar, although these two drugs differ substantially in their chemical structures.…”
Section: Resultsmentioning
confidence: 99%
“…One, cilostazol, with antiplatelet, antithrombotic, and vasodilatory effects, has been approved for the treatment of patients with intermittent claudication (Dawson, 2001) and for prevention of short-and mediumterm vessel closure as well as late restenosis after intracoronary stenting (El-Beyrouty and Spinler, 2001;Tanabe et al, 2001). The other, milrinone, improves the hemodynamic status of heart failure via inotropic/vasodilatory effects attributable to the increase in cardiac intracellular cAMP level (Kishi et al, 2001). Milrinone is used for the treatment perioperative severe heart failure or marked deterioration of congestive heart failure (Kikura and Levy, 1995).…”
mentioning
confidence: 99%
“…23) Milrinone is considered to exert a positive inotropic action and to decrease left ventricular endsystolic pressure reflecting the decrease in left ventricular afterload. 24) However, milrinone-induced reductions in effective arterial elastance reflecting the fall in total peripheral resistance and changes in stroke volume are not significant. 24) These previous reports suggested that baroreflex control is important to obtain the inotropic effect of milrinone.…”
Section: Discussionmentioning
confidence: 98%
“…24) However, milrinone-induced reductions in effective arterial elastance reflecting the fall in total peripheral resistance and changes in stroke volume are not significant. 24) These previous reports suggested that baroreflex control is important to obtain the inotropic effect of milrinone. Another previous study suggested that BRS predicts the cases in which milrinone increases left ventricular dp/dt.…”
Section: Discussionmentioning
confidence: 98%